DAMPAK LATIHAN DAN DIET TERHADAP RISIKO SINDROM METABOLIK - Reshandi Nugraha, - (2022)
A metabolic syndrome is a group of health disorders that coincide, including three of the five components: triglycerides, HDL, Blood Sugar, Waist Circumference, and Blood Pressure exceeding average limit values. The risk of metabolic syndrome can unconsciously occur in someone who experiences weight gain dominated by fat. This study aims to determine the impact of exercise and diet on the risk of metabolic syndrome. The research method used in this study is an experimental study with a 3x2 factorial design, the exercise model as an independent variable consisting of 3 classifications, namely aerobic exercise, anaerobic exercise, and combined exercise, while diet as a moderating variable consists of two classifications, namely calorie restriction, and exercise. Non-calorie restriction. The dependent variable in this study is metabolic syndrome, including HDL, LDL, total cholesterol, triglycerides, blood pressure, waist circumference, and blood sugar levels. There were six experimental groups which included aerobic exercise and calorie restriction (A1B1), anaerobic exercise and calorie restriction (A2B1), combined exercise and calorie restriction (A3B1), aerobic exercise and non-diet (A1B2), anaerobic and non-dietary exercise ( A2B2), combined exercise and non-diet (A3B2). Data analysis in this study used two-way ANOVA statistical analysis. The results of this study indicate that there are differences in the effect of exercise on reducing the risk of metabolic syndrome, there are differences in the effect of diet on reducing the risk of metabolic syndrome, and there is an interaction between exercise and diet that affects reducing the risk of metabolic syndrome. Combined exercise has the most significant effect on reducing the risk of metabolic syndrome compared to aerobic exercise and weight training, calorie restriction diet is more influential in reducing the risk of metabolic syndrome than non-diet, and there is an interaction between exercise and diet that affects reducing the risk of metabolic syndrome. To prevent or treat metabolic syndrome, one can apply exercise combined with diet, but to get optimal results in reducing the risk of metabolic syndrome can apply combined exercise and calorie restriction.